2018
DOI: 10.1093/mnras/sty1747
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the kinematics of the discs around Galactic B[e] supergiants

Abstract: B[e] Supergiants are luminous evolved massive stars. The mass-loss during this phase creates a complex circumstellar environment with atomic, molecular, and dusty regions usually found in rings or disk-like structures. For a better comprehension of the mechanisms behind the formation of these rings, detailed knowledge about their structure and dynamics is essential. To address that, we obtained high-resolution optical and near-infrared spectra for 8 selected Galactic B[e] Supergiants, for which CO emission has… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 60 publications
8
50
0
Order By: Relevance
“…The distance to Hen 3-365 is uncertain and contributes to the unknown evolutionary status of the star. The extinction and kinematics indicate that Hen 3-365 is more likely an evolved supergiant at a distance of several kpc than a close young star (Oudmaijer et al 1998), andMaravelias et al (2018) classify Hen 3-365 as a massive supergiant. However the HI column density is far too high for Hen 3-365 to be a supergiant (Oudmaijer et al 1998).…”
Section: Hen 3-365 (Hd 87643)mentioning
confidence: 99%
“…The distance to Hen 3-365 is uncertain and contributes to the unknown evolutionary status of the star. The extinction and kinematics indicate that Hen 3-365 is more likely an evolved supergiant at a distance of several kpc than a close young star (Oudmaijer et al 1998), andMaravelias et al (2018) classify Hen 3-365 as a massive supergiant. However the HI column density is far too high for Hen 3-365 to be a supergiant (Oudmaijer et al 1998).…”
Section: Hen 3-365 (Hd 87643)mentioning
confidence: 99%
“…With the identification of the lines of [Ca II] λλ7291,7324 in the spectra of numerous B[e]SGs, a further highly valuable tracer for the disk kinematics has been found. These lines typically display double-peaked profiles as well, with velocities comparable to or even greater than the one traced by the [O I] λ5577 line ( [53,57,58]). This implies that they form in the same region, or at least very close to each other, which is in agreement with their comparably high critical density.…”
Section: Disk Dynamics and Structurementioning
confidence: 99%
“…While, in general, the rotational motion of the material within the circumstellar disks of B[e]SGs seems now to be well established, maybe in connection with a (very) slow outflow component ( [57]), recent investigations of the spatial distribution of the circumstellar gas revealed that it is more likely accumulated in multiple rings, partial rings, and possible spiral arm-like structures rather than in a smooth disk ( [43,44,58]). These rings might result from multiple mass ejection phases caused by (pulsational) instabilities acting in the outer layers of these luminous objects (e.g., [73][74][75]), or from binary interaction in close systems as seems to be the case for some of the Galactic objects ( [58]) in which the rings are circumbinary rather than circumstellar. Other disk-forming mechanisms that have been proposed in the literature over the years include equatorial mass-loss from a critically rotating star ( [76,77]), the rotationally induced bi-stability mechanism ([78]), the slow-wind solution ( [79]), and the combination of the latter two ( [80]).…”
Section: Disk Dynamics and Structurementioning
confidence: 99%
“…Within the discs, the molecules are shielded from the dissociating stellar ultraviolet radiation field. Emission from hot CO gas has been detected in the IR spectra of both accretion discs of pre-main sequence stars (e.g., Geballe & Persson 1987;Carr 1989Carr , 1995Wheelwright et al 2010;Ilee et al 2013Ilee et al , 2018 and discs formed from the outflows and ejecta of evolved massive stars such as the B[e] supergiants (McGregor et al 1988a(McGregor et al ,b, 1989Morris et al 1996;Wheelwright et al 2012;Kraus et al 2016Kraus et al , 2017Torres et al 2018;Maravelias et al 2018;Kourniotis et al 2018). Enrichment in 13 CO has been found, based on measurements of the 12 CO/ 13 CO ratio in high-quality near-IR spectra, solely in the discs of confirmed evolved objects (Liermann et al 2010;Oksala et al 2013;Kraus et al 2013bKraus et al , 2014, reinforcing the power of this isotope-ratio method for the discrimination between young and evolved stars (Muratore et al 2015).…”
Section: Introductionmentioning
confidence: 99%